Fokusace očí na charakteristické prvky vizuálního vjemu - Fejgl, Martin (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2011)
Tato diplomová práce se zabývá fyziologií svalů pro pohyb oka a problematikou měření povrchové elektromyografie. Je zde vysvětlena fyziologie a analýza očních pohybů. Dále se práce zabývá různými způsoby měření elektrookulografu a následným vyhodnocením naměřeného signálu.

This master’s thesis deals with muscles physiology of eye movement and questions of surface electromyography measurement. Physiology and analysis of eye movement are described here. Furthermore the paper deals with a variety of electrooculographic measuring techniques and also with resulting evaluation of measured signal.
Focusation of eyes on characteristic component of visual perception.
Keywords: Elektrookulografie; elektromyografie; oko; oční pohyby; Electrooculography; electromyography; eye; eye movements